Wpływ ludności napływowej na funkcjonowanie szkolnictwa województwa śląskiego w latach 1945-1950 = The significance of the transfer of people for the system of education in the Upper Silesia in the years 1945-1950 - Fic, Maciej (Zielona Góra: Lubuskie Towarzystwo Naukowe)
The paper presents the influence of the immigrants on the functioning of the system of education in the Silesian Province during the first ten years after the end of World War II. The author describes the changes which took place among the teaching staff (while indicating at the problems of the remaining autochthonous population and immigrant teachers or implementing new educational aims with the support of the new group of learners) as well the advantages and drawbacks of the process of education of children from various social environments (as well as the relations among them).
Keywords: województwo śląskie; migracje; imigranci; szkolnictwo; Górny Śląsk; 1945-1950